Capitalism, Lakouism, and Libertarian Communism - Mocombe, Paul C. (Cambridge Scholars Publisher, 2020)
This work highlights the Haitian sociopolitical economic organization, Lakous. It posits that the Lakou is a form of libertarian communism that must be vertically integrated at the nation-state level so that the people can experience total freedom from neoliberal capitalist relations of production and their deleterious effects, such as exploitation and climate change.